Respuesta :

6x-15=3(4x+3)
Distribute the three to the parentheses
6x-15=12x+9
Transfer the 6 over to the 12 by subtracting it
-15=6x+9
Subtract 9 from 15
-24=6x
Then divide the six by the -24
X=-4

[tex]6x - 15 = 3(4x + 3) [/tex]
then you distribute the three
so you would do
[tex]3 \times 4x = 12x[/tex]
[tex]3 \times 3 = 9[/tex]
[tex]6x - 15 = 12x + 9[/tex]
then you get the variables on the same side
[tex] - 6x[/tex]
on each side so you would have 6x on the right side then you subtract the nine so you would have -24 on the left side so now you have
[tex] - 24 = 6x[/tex]
then you divided by 6 which the answer equals
[tex]x = - 4[/tex]
ACCESS MORE